SYNERGY OF TECHNOLOGIES IN TEACHING MATHEMATICS - NOVÁK, Michal (Journal of Technology and Information Education, 2012)
The article gives an overview of professional mathematical software which students entering universities of technology are likely to use from the very beginning of their engineering studies. The article is intended as information for secondary school teachers who would like to make the transition between secondary school and university easier for their students. The software is discussed from the point of view of accessibility of the content rather than functionality. Differences of approach to preparing and distributing content are also discussed. Some suggestions of didactic use of respective products are also included.
Keywords: ICT in teaching mathematics; Maple; Mathematica; mathematical software; MATLAB